PENGAWASAN ANGKUTAN KOTA OLEH DINAS PERHUBUNGAN KOTA DUMAI - Faisal Yunan Siregar; Ernawaty " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
City Transportation stipulated in the Decree of the Minister of Transportation KM numbers. 35 of 2003 on the implementation of the road transport by public transport. The ministerial decree contains provisions in urban transportation. Problems that occur in Dumai still many Urban Transport netted in public passenger and freight operations were caught violating the license should be completed throughout the City Transportation partly also ineligible roadworthy this can cause problems with regard to the safety of passengers and road users other. Public confidence to use the City Transport began to diminish due to inconvenience in use. This is because of several City Transport which is not according to the standard of driving is reckless, smoking, stop halfway etc. Things like this which should be addressed by the Department of Transportation. So that people do not feel reluctant to use public facilities in transportation services. Improve oversight by observing impose sanctions and an evaluation of public transport that does not meet the criteria specified in the regulations. In imposing sanctions for drivers need good firmness and City Transport to the City Transportation companies provide socialization is because of weak regulatory oversight of public transport is also affected by the lack of knowledge of the Municipal Transport driver itself on the City Transportation standards.Keywords: Supervision, Sanctions, Evaluation